Effects of water-fertilizer coupling on root distribution and yield of Chinese Jujube trees in Xinjiang - Hongguang, Liu; Xinlin, He; Jing, Li; Fadong, Li; Ping, Gong; Jie, Zhang; Guang, Yang (International Journal of Agricultural and Biological Engineering, 2017)
Water and fertilizer are the two main factors which promote the rapid growth of Jujube (Ziziphus jujuba) trees. Studies of root systems and the nutrition-use efficiency of dense, dwarfed fruit trees are limited, especially in an extremely arid region with drip irrigation. The experiment was conducted in a 12-year-old dwarf jujube planting basement in Hami from 2013 to 2015. In this experiment, root length density and root weight density were calculated and found to range from 75 cm to 275 cm in horizontal distance, and from 0 to 90 cm in vertical depth, treated with three drip irrigation quota gradients and three fertilizer rates with each treatment replicated three times. The results showed that, as the amount of nitrogen applied increased gradually, the jujubes’ growth amount increased, reaching a maximum when an optimal concentration was applied. However, the jujubes’ growth was inhibited, and the growth declined when the amount of nitrogen applied was more than the optimal concentration. At an appropriate level of nitrogen, the growth, yield and quality of jujube trees could be guaranteed. If the rate of nitrogen application was lowered, the jujubes’ growth would inhibit, and hence the yield wound be seriously impacted. The optimal irrigation quota and fertilization amount were found to be 900 mm and 1500-1800 kg/hm2, respectively. The research findings were of significance and hold great promise for the development of the forestry and fruit industries in the arid region of Xinjiang. At the same time, there was a further study on irrigation technique, focusing on the combined effect of the dwarfed-planting technique and drip irrigation on jujube trees; with this information, the application efficiency of water and fertilizer can be optimized, leading to higher profits and economic efficiency.Keywords: water-fertilizer coupling, root distribution, yield, dense dwarf trees, Ziziphus jujubaDOI: 10.25165/j.ijabe.20171006.3109Citation: Liu H G, He X L, Li J, Li F D, Gong P, Zhang J, et al. Effects of water-fertilizer coupling on root distribution and yield of Chinese Jujube trees in Xinjiang. Int J Agric & Biol Eng, 2017; 10(6): 103–114.